A seventeenth-century odyssey in East Central Europe : the life of Jakab Harsanyi Nagy - Kármán, Gábor. (The History of Oriental Studies, 2016)
In A Seventeenth-Century Odyssey Gábor Kármán reconstructs the life story of a lesser-known Hungarian orientalist, Jakab Harsányi Nagy. The discussion of his activities as a school teacher in Transylvania, as a diplomat and interpreter at the Sublime Porte, as a secretary of a Moldavian voivode in exile, as well as a court councillor of Friedrich Wilhelm, the Great Elector of Brandenburg not only sheds light upon the extraordinarily versatile career of this individual, but also on the variety of circles in which he lived. Gábor Kármán also gives the first historical analysis of Harsányi's contribution to Turkish studies, the Colloquia Familiaria Turcico-latina (1672).